Catalytic wet air oxidation of butyric acid solutions using carbon supported iridium catalysts - Gomes, Helder (2010)
The search for new advanced cleanup catalytic technologies imparted to catalytic wet air oxidation (CW AO) a recrudescent interest in recent years. At the present, more than 100 plants using CW AO are operative worldwide, mainly for treatment of streams from petrochemical, chemical, pharmaceutical and textile industries. CWAO can be used either for complete oxidative degradation, or as pre-treatment for biological degradation of downstream waste waters. On the other hand, it· can also be used to act locally, on a specific pollutant upstream, aiming at recycling of waters and reduction of wastes. In this case, knowing the reaction mechanisms and reliable kinetics for the degradation of model compounds is of great importance. Butyric acid is known to oxidize at a significant rate under very severe conditions of pressure, temperature and residence times in the traditional non-catalytic wet air oxidation. These demanding conditions prompted us to develop heterogeneous catalysts, more efficient at milder conditions.